Quantifying the Effects of Ethanol and Temperature on the Fitness Advantage of Predominant Saccharomyces cerevisiae Strains Occurring in Spontaneous Wine Fermentations - Ganucci, Donatella; Guerrini, Simona; Mangani, Silvia; Vincenzini, Massimo; Granchi, Lisa (Frontiers in Microbiology, 2018)
Different Saccharomyces cerevisiae strains are simultaneously or in succession involved in spontaneous wine fermentations. In general, few strains occur at percentages higher than 50% of the total yeast isolates (predominant strains), while a variable number of other strains are present at percentages much lower (secondary strains). Since S. cerevisiae strains participating in alcoholic fermentations may differently affect the chemical and sensory qualities of resulting wines, it is of great importance to assess whether the predominant strains possess a “dominant character”. Therefore, the aim of this study was to investigate whether the predominance of some S. cerevisiae strains results from a better adaptation capability (fitness advantage) to the main stress factors of oenological interest: ethanol and temperature. Predominant and secondary S. cerevisiae strains from different wineries were used to evaluate the individual effect of increasing ethanol concentrations (0-3-5 and 7% v/v) as well as the combined effects of different ethanol concentrations (0-3,5 and 7% v/v) at different temperature (25-30 and 35°C) on yeast growth. For all the assays, the lag phase period, the maximum specific growth rate (µmax) and the maximum cell densities were estimated. In addition, the fitness advantage between the predominant and secondary strains was calculated. The findings pointed out that all the predominant strains showed significantly higher µmax and/or lower lag phase values at all tested conditions. Hence, S. cerevisiae strains that occur at higher percentages in spontaneous alcoholic fermentations are more competitive, possibly because of their higher capability to fit the progressively changing environmental conditions in terms of ethanol concentrations and temperature.